Upaya Guru Pendidikan Agama Islam dalam Pembentukan Karakter Siswa yang Berakhlak Mulia - fadlan, Fadlan Taufiqurrohman (Progressive of Cognitive and Ability, 2022)
Islamic Religious Education teachers play an important role in shaping the character of students in schools. The role of the Islamic Religious Education Teacher is to shape the character of students who were not good enough to become better, and before that were good to become even better. The purpose of this study was to determine the efforts of Islamic religious education teachers in shaping the character of students at Ponpes K.H Ahmad Dahlan Sipirok. The research that the author is doing is field research using a qualitative approach. Data was collected by conducting observations, interviews, and documentation. The results of the study show that the efforts of Islamic religious education teachers in forming student character are: Cooperation with parents is important so how children can become or have good character there must be cooperation with parents and the surrounding environment, and the purpose of extracurricular activities provides an overview of how character students are built well, then the supporting and inhibiting factors of the teacher in shaping the character, the existence of adequate facilities in shaping the character of the students. The obstacle is from the students themselves, where it seems that students have good character at school but when at home the environment is not supportive or lacks parental supervision.